Adverse reaction to silicone simulating orofacial granulomatosis. (21st April 2014) - Requena, C.; Requena, L.; Alegre, V; Serra, C.; Llombart, B.; Nagore, E.; Guillén, C.; Sanmartín, O.
Abstract: Background: Granulomatous reactions to silicone facial fillers are well described in the literature. Clinically, these reactions present as nodules or pseudotumors that are frequently described as silicone granulomas or siliconomas. Objective: We want to report a peculiar form of granulomatous reaction to injected silicone characterized by recurrent episodes of facial edema. Methods: We collected silicone infiltrated patients with a similar clinical picture consisting of asymptomatic episodes of unilateral facial edema that had been recurring for months or years. Results: We found four women with recurrent episodes of facial edema. They had been infiltrated with silicone in the face. Histology showed silicone deposits and a granulomatous infiltrate in all 4 cases. Conclusion: We describe and illustrate a new type of adverse reaction to injected silicone simulating orofacial granulomatosis. The reaction presents as recurrent, unilateral, asymmetric facial edema of the cheek in patients who have been injected with silicone in the face. Familiarity with this adverse reaction will help to prevent erroneous diagnoses such as idiopathic angioedema, Melkersson Rosenthal syndrome, and orofacial granulomatosis.